STUDI EKSPERIMENTAL REACTIVE POWDER CONCRETE (RPC) - ISTIQOMAH
Reaktive Powder Concrete (RPC) is a new kind concrete that posses an ultra high compressive strength (200 Mpa to 800 Mpa). The primary component of RPC is very fine powder that has high silica content, which is aimed to perfect the concrete's chemical reaction and to improve homhgeneity. Reacti powder Concrerte is a mixture of cement, silica fume, 300 Âµm diameter maximum of quartz, superplasticizer and steel fiber to improve ductility. With its high strength and high ductility, RPC has potensial of replacing steek foconstruction material.The abundant availability of local material, such as silica and quartz, makes RPC a very potential alternative material for Indonesia. This research is an attempt to develop the first Reactive Powder concrete in Indonesia based on report by various researches. Laboratory experiment was conducted to produce RPC mixture using locally available material.1. At this early attempt, the experiment has yet to successfully accomplish the desired target. This failure is attributed to different composition and charateristic of superplasticizer , silica fume and cement.